A Screening of Mucin-Producing Cells and Structures, from Digestive System, in Rats - Ilinca IOZON; Adrian-Florin GAL; Maria-Cătălina MATEI LAȚIU; Vasile RUS; Cristian RAȚIU; Laura Cristina ȘTEFĂNUȚ (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Veterinary Medicine, 2023)
A screening and a morphological analysis of mucin-producing cells and structures, from the digestive tract, in rats, will further allow to quantify their local and systemic response. 10 Wistar rats were selected for this study. Sections of the sublingual gland, Weber's gland, stomach, jejunum and colon were taken. The samples were stained by the Trichrome Goldner technique. Based on the histological examination, both morphometric and statistical analysis were performed using specific software’s (ToupView Soft and GraphPad Prism Software). The histological examination showed normal characteristics for the analyzed cells and structures. The test for the normal distribution of the data revealed that they are normally distributed and statistical comparison between cell surfaces suggested a significant difference between means with p˂0.0001. Moreover, statistically significant differences were observed between the areas of Weber gland acini and those of sublingual gland acini (p<0.05). Based on our results we can conclude that the observed differences, regarding the cellular surfaces, are in accordance with the physiological characteristics of each analyzed structure.